2020
DOI: 10.1037/pst0000288
|View full text |Cite|
|
Sign up to set email alerts
|

Positivity pays off: Clients’ perspectives on positive compared with traditional cognitive behavioral therapy for depression.

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Moreover, these treatments may able to target both devaluation of positivity and rumination, given that those who have a tendency to dampen their positive affect also engage in more rumination of negative affect (Feldman et al, 2008). Recently developed positive affect treatments have shown promising results (Craske et al, 2019; Dunn, Widnall, Reed, Owens, et al, 2019; Dunn, Widnall, Reed, Taylor, et al, 2019; Geschwind et al, 2020; Taylor et al, 2017), including increases in positive affect and decreases in negative affect (for a review, see Winer et al, 2019). Although positive affect treatments do not specifically target rumination, they target negative cognitions that may interfere with their ability to experience and savor positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these treatments may able to target both devaluation of positivity and rumination, given that those who have a tendency to dampen their positive affect also engage in more rumination of negative affect (Feldman et al, 2008). Recently developed positive affect treatments have shown promising results (Craske et al, 2019; Dunn, Widnall, Reed, Owens, et al, 2019; Dunn, Widnall, Reed, Taylor, et al, 2019; Geschwind et al, 2020; Taylor et al, 2017), including increases in positive affect and decreases in negative affect (for a review, see Winer et al, 2019). Although positive affect treatments do not specifically target rumination, they target negative cognitions that may interfere with their ability to experience and savor positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…Positive emotions can constitute ongoing personal resources to draw from when confronted with unavoidable stressful events in later times, such as experiences of loss, typically associated to depression and negative emotions, or of a threat, typically associated to stress and anxiety. Along these lines, interestingly, in a recent study, patients with depression who were offered either traditional CBT or positive cognitive behavioral therapy (i.e., CBT focused on positive emotions and strengths) found positive CBT more pleasant and motivating, showing that paying explicit attention to positive affect in psychotherapy is rewarding, and can help to better treat depression (Geschwind et al 2020). The strong and positive association between positive affect and compassion in our findings shows that a compassionate attitude toward our fellow human beings may help us to experience more emotions that are positive and constitute a buffer against depression.…”
Section: Discussionmentioning
confidence: 99%
“…Geschwind showed that intervention with CBT in depress patient has good results and increases their optimism. [ 28 ] Amir Soleimani's studies[ 9 ] showed the effectiveness of cognitive-behavioral therapy on the optimism score in female students compared to the control group. Cognitive-behavioral therapy leads to a slight increase in positive psychology.…”
Section: Discussionmentioning
confidence: 99%